'Sweet as a Nut': Production and use of nanocapsules made of glycopolymer or polysaccharide shell. (September 2021) - Yan, Xibo; Chai, Luxiao; Fleury, Etienne; Ganachaud, François; Bernard, Julien
Abstract: Polymeric nanomaterials are deemed to unlock the potential of therapeutics and improve their efficiency, to allow future advances in nanomedicine. Among these, sugar-based nanocapsules made of synthetic or natural carbohydrate-based macromolecular chains have raised significant interest in bio-applications. This review highlights physical or/and chemical techniques to construct both water- and oil-filled sugar-based nanocapsules. These include soft matter processes, such as (double) emulsification, coacervation or layer-by layer fabrication as well as more recently developed processes such as Polymerization Induced Self Assembly (PISA) or template core removal. Properties and bio-applications of glyconanocapsules (GNCs) are summarized and open challenges as well as opportunities for the future development of this field are being discussed. Graphical abstract: Image, graphical abstract